Practical Consensus Recommendations for Optimizing Risk versus Benefit of Chemotherapy in Patients with HR Positive Her2 Negative Early Breast Cancer in India - Parikh, Purvish M.; Bhattacharyya, Gouri Shankar; Biswas, Ghanshyam; Krishnamurty, Arvind; Doval, Dinesh; Heroor, Anil; Sharma, Sanjay; Deshpande, Ramakant; Chaturvedi, Harit; Somashekhar, S. P.; Babu, Govind; Reddy, G. Krishna; Sarkar, Diptendra; Desai, Chirag; Malhotra, Hemant; Rohagi, Nitesh; Bapna, Ajay; Alurkar, S. S.; Krishna, Prasad; Deo, S. V.S.; Shrivastava, Anurag; Chitalkar, Prakash; Majumdar, Saroj Kumar; Vijay, Devanhalli; Thoke, Aniket; Udupa, K. S.; Bajpai, Jyoti; Rath, G. K.; Dattatreya, Palanki Satya; Bondarde, Shailesh; Patil, Shekhar (South Asian Journal of Cancer, 2021)
Breast cancer is a public health challenge globally as well as in India. Improving outcome and cure requires appropriate biomarker testing to assign risk and plan treatment. Because it is documented that significant ethnic and geographical variations in biological and genetic features exist worldwide, such biomarkers need to be validated and approved by authorities in the region where these are intended to be used. The use of western guidelines, appropriate for the Caucasian population, can lead to inappropriate overtreatment or undertreatment in Asia and India. A virtual meeting of domain experts discussed the published literature, real-world practical experience, and results of opinion poll involving 185 oncologists treating breast cancer across 58 cities of India. They arrived at a practical consensus recommendation statement to guide community oncologists in the management of hormone positive (HR-positive) Her2-negative early breast cancer (EBC). India has a majority (about 50%) of breast cancer patients who are diagnosed in the premenopausal stage (less than 50 years of age). The only currently available predictive test for HR-positive Her2-negative EBC that has been validated in Indian patients is CanAssist Breast. If this test gives a score indicative of low risk (< 15.5), adjuvant chemotherapy will not increase the chance of metastasis-free survival and should not be given. This is applicable even during the ongoing COVID-19 pandemic.
Keywords: avoiding financial distress; avoiding toxicity; COVID-19; low- and middle-income countries; personalized therapy; precision oncology; saving lives